Ergonomics Simulation and Analysis of Specially Designed Chair - Shahrol, Mohamaddan; Aliff, Rahman; Musdi, Shanat; Siti Zawiah, Md Dawal; Akihiko, Hanafusa (2022)
Chair comes in different sizes and shapes depending on the functions as well as the users involved. However, the designers seldom consider the ergonomics aspect in chair design. This research has been conducted as a case study to compare and select the best design parameters within two chairs known as Chair A and B using human modelling software called AnyBody. Different parameter was manipulated in the simulation which is backrest angles for Chair A and seat heights for Chair B. A total of ten chairs with different parameters (five from Chair A and five from Chair B) were conducted in the simulation. Results were generated through inverse dynamics analysis in the form of muscle activities envelopes and reaction force on vertebrae L4 to L5. The result shows that 80° backrest was the best ergonomics design for Chair A while 0.30 m seat height was the best ergonomics design for Chair B. The simulation conducted is important as an early ergonomics intervention before the real chair fabrication is conducted.